The New Topology of Multi Level Inverter with Minimum of Switches (International Journal of Innovative Research in Computer Science & Technology, 2022)
A new multilayer inverter topology is  proposed in this study. The cascaded feature is used in this  innovative topology. In addition to the isolated DC sources  seen in Cascaded H-bridge. The clamping diode in Diode  and the multilevel inverter (CHB-MLI) Inverter with  Clamped Multilevel (DC-MLI). With these advantages, an inverter topology with 18 total component counts when  coupled had been discovered. This proposed topology has  the potential to generate up to According to the ratio  allocated to its DC sources, there are 17 output levels.  Aside from increasing the number of output voltage levels,  this study has a relatively low number of component  counts. The THD limit defined by IEEE standard is also a  goal (i.e. 5 percent) all voltage applications under 69kV.To  ensure that the suggested topology is functional, it is being  simulated in Matlab/Simulink with various modulation  indexes. The amount of THD, the number of voltage  outputs, and the RMS voltage are all being monitored and  discussed. Finally, to assess the uniqueness of the  suggested topology, a comparison study with recently  disclosed topologies is being carried out.
Keywords: Topology; THD; multi-level Inverter; DC